Old Masters, New Meanings - Danny Wildemeersch (Universidade de Lisboa, 2020)
Emancipatory education became an important notion for critical pedagogues from the sixties and seventies of the 20th century onwards. Various 'old masters' then inspired educationalists with their interpretation of this concept. Today, times have profoundly changed. The question now is whether these interpretations are still valid. Is there a need to reconsider them? To what extent are the ideas of 'the old masters' still useful? What elements are outdated? Six contributions engage with these questions reminding us of the ideas of Paulo Freire, John Dewey, Bruno Latour, Ivan Illich, Jacques Rancière and Axel Honneth.